2012
DOI: 10.1371/journal.pone.0049121
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Reward Is Increased after Roux-en-Y Gastric Bypass in Dietary Obese Rats with Differential Effects following Ghrelin Antagonism

Abstract: Roux-en-Y gastric bypass (RYGB) is one of the most successful treatments for severe obesity and associated comorbidities. One potential adverse outcome, however, is increased risk for alcohol use. As such, we tested whether RYGB alters motivation to self-administer alcohol in outbred dietary obese rats, and investigated the involvement of the ghrelin system as a potential underlying mechanism. High fat (60%kcal from fat) diet-induced obese, non-diabetic male Sprague Dawley rats underwent RYGB (n = 9) or sham o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 71 publications
6
57
2
Order By: Relevance
“…Ghrelin itself shows reinforcement properties akin to drugs of abuse by causing increases in locomotion, release of dopamine in the accumbens, and induction of conditioned place preference (Jerlhag, 2008). In the current study, although in agreement with previous works showing DLys reduces ethanol intake (Kaur and Ryabinin, 2010; Hajnal et al, 2012), the effect was only seen 4-hours post-injection on the first day. In a previous study from our lab, it was shown that following a 4-hour 2-bottle ethanol access, mice treated with DLys show decreased drinking and associated lower blood ethanol contents (BEC).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ghrelin itself shows reinforcement properties akin to drugs of abuse by causing increases in locomotion, release of dopamine in the accumbens, and induction of conditioned place preference (Jerlhag, 2008). In the current study, although in agreement with previous works showing DLys reduces ethanol intake (Kaur and Ryabinin, 2010; Hajnal et al, 2012), the effect was only seen 4-hours post-injection on the first day. In a previous study from our lab, it was shown that following a 4-hour 2-bottle ethanol access, mice treated with DLys show decreased drinking and associated lower blood ethanol contents (BEC).…”
Section: Discussionsupporting
confidence: 93%
“…Kaur and Ryabinin (2010) found DLys reduces ethanol intake and preference, while also blocking ethanol-induced c-Fos expression in the Edinger-Westphal nucleus, a region affiliated with ethanol sensitivity and intake. DLys has also been shown to block ethanol reward seeking in rats (Hajnal et al, 2012). JMV2959 is a small molecule-type specific antagonist of ghrelin receptors (Moulin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a follow up study directly investigating changes in alcohol reward (Hajnal et al ., 2012), high fat diet-induced obese rats underwent RYGB or sham operation and were tested 4 months after surgery on a progressive ratio schedule of reinforcement operant task for 2, 4, and 8% EtOH. Compared to sham-operated controls, RYGB rats made significantly more efforts to earn access to alcohol reward, and also consumed more when it was available.…”
Section: Bariatric Surgery As a Risk For Audmentioning
confidence: 99%
“…Because of the possibility of functional recovery following genetic deletion of the receptor, Experiment 2 investigated the role of ghrelin in glucose conditioning by using the ghrelin receptor antagonist (D-Lys3)-GHRP-6. This antagonist is reported to decrease food intake, high-fat diet preference, alcohol intake, body weight, and lever pressing for food in rodents [2,17,18,19,21,24,25]. Here we determined if treating WT mice with (D-Lys3)-GHRP-6 during training sessions with CS+/GLU and CS−/S+S solutions altered their acquisition of a CS+ flavor preference.…”
Section: Experiments 2 Flavor Conditioning By Oral Glucose In Micementioning
confidence: 99%